HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN TINGKAT KEPATUHAN DALAM MENJALANKAN KEMOTERAPI PADA PASIEN KANKER KOLOREKTAL DI RUANGAN GB3A MURNI TEGUH MEMORIAL HOSPITAL - Purba, Olivia Artasari; Seriga Banjarnahor (JOURNAL SAINS STUDENT RESEARCH, 2025)
Background: Cancer is a non-communicable disease characterized by malignant abnormal cells or tissue that quickly get out of control and can spread to other parts of the sufferer's body. Chemotherapy therapy has side effects that significantly impact patients both physically and psychologically, so it can affect the compliance of colorectal cancer patients in undergoing chemotherapy. Various factors can influence the management of colorectal cancer patients receiving chemotherapy, such as family support and poor patient knowledge. Objective: To determine the factors that influence the level of compliance in carrying out chemotherapy in colorectal cancer patients in Room GB3A, Murni Teguh Hospital, Medan, in 2023, mainly family support and knowledge. Method: This research is quantitative research with a retrospective method. A chi-square test was used in this study. The independent variables in this research are family support and knowledge, which is seen based on the questionnaire. The dependent variable is the compliance of colorectal cancer patients with chemotherapy, as seen from the amount of chemotherapy received by the patient. Results: This study shows a significant effect of family support and knowledge, namely 0.000 (p < 0.05). Conclusion: Some factors influence family support and knowledge factors on colorectal cancer patients' compliance with chemotherapy in the GB3A Murni Teguh Memorial Hospital Medan room.